Equality, Difference, and the Possibility of Peaceful Coexistence: A Critical Review of the Book Can We Live Together? Equality and Difference - Aliashraf Nazari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In global societies whose issues have affected all aspects of private and public life, we are witnessing the spread of populist and specialist processes. On the one hand, we are witnessing growing universalism and homogeneity, and on the other, identity groups in the form of particularism and construct various forms of nationalism and a sense of religious, cultural, ethnic and political belonging. Providing an appropriate response to such a situation becomes even more important when we see the fragmentation of experience, fluidity and constant change, the importance of large financial, technological and media organizations instead of institutions, the end of the age of order, and we are at the beginning of the age of change and the rise of the risk society. Influenced by such a dual situation in which universalism (in the form of common moral-political values) and particularism (the independence of minorities and communities) are confronted with the question of how can we live and interact with each other? is very important. These responses, in the form of reviving the specific practices of the past, creating a world free of time and space constraints and preserving differences, and resorting to a kind of procedural democracy with the aim of accepting the rules of the game, ensuring respect for individual and collective freedoms and the institutionalization of tolerance are presented. The three central positions of the book are the subject, intercultural communication, and democracy. The starting point of the book is the personal subject, the path it takes, the intercultural connection and its goal, democracy. The main purpose of this article is to describe critique and evaluate the book Equality and Difference; can we live together?